2001
DOI: 10.2519/jospt.2001.31.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Tibial Translation During Different Isokinetic Quadriceps Torque in Anterior Cruciate Ligament Deficient and Nonimpaired Individuals

Abstract: Study Design: Factorial quasi-experimental design. Objectives: To quantify the effect of different levels of isokinetic concentric and eccentric knee extensor torques on the anterior tibial translation in subjects with anterior cruciate ligament (ACL) deficiency. Electromyogram (EMG) activity of 4 leg muscles was recorded in order to detect any co-activation of extensors and flexors. Background: The rehabilitation after an ACL injury is of importance for the functional outcome of the patient. In order to const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 12 publications
2
29
0
2
Order By: Relevance
“…45,139 While it is difficult to draw unequivocal conclusions from the conflicting evidence following surgical reconstruction of the torn ACL, it appears that eccentric hamstring strength is impaired after ACL reconstruction. 105,108,123 As well, quadriceps weakness following ACL reconstruction is also variable 105,108 and somewhat dependent on the numerous rehabilitation and testing protocols used, making it difficult to draw any consensus from the literature. Clearly, however, eccentric muscle dysfunction does exist around unstable (and painful 141 ) joints, and therefore must be reversed.…”
Section: Joint and Ligament Injuries: Prevention And Management Consimentioning
confidence: 99%
“…45,139 While it is difficult to draw unequivocal conclusions from the conflicting evidence following surgical reconstruction of the torn ACL, it appears that eccentric hamstring strength is impaired after ACL reconstruction. 105,108,123 As well, quadriceps weakness following ACL reconstruction is also variable 105,108 and somewhat dependent on the numerous rehabilitation and testing protocols used, making it difficult to draw any consensus from the literature. Clearly, however, eccentric muscle dysfunction does exist around unstable (and painful 141 ) joints, and therefore must be reversed.…”
Section: Joint and Ligament Injuries: Prevention And Management Consimentioning
confidence: 99%
“…Extension and flexion strength after ACL rupture is assessed by isokinetic dynamometry, which involves measurements mainly of the classical parameters such as peak torque, total work and average power (Benjuya et al, 2000;St. Claire Gibson et al, 2000;Kvist et al, 2001;Verdonck et al, 1994;Wu et al, 1997). This conventional approach is, however, inadequate for the assessment of the quality of torque production throughout the range of motion.…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons might be that ACLD subjects allow shear displacement in the knee. Kvist et al [17] have examined anterior shear displacement during isokinetic knee extensions and they found that the absolute translation was larger in ACLD subjects. By allowing shear displacement, secondary restraining structures can balance the shear force.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few isokinetic or isometric studies have been done on ACLD subjects. Osternig et al [19] found more co-contraction in the injured leg, while others found no co-contraction [17] or no difference in co-contraction between normal and ACLD subjects [9].…”
Section: Introductionmentioning
confidence: 95%